Implementasi Program Deteksi Dini Stunting Di Posyandu: Tinjauan Terhadap Sikap Dan Motivasi Kader - Yuli Rahayu; Nurul Ilmi; Ani Asram (Window of Public Health Journal, 2026)
The early detection of stunting program is an important strategy in stunting prevention efforts at the community level through the role of integrated health post (Posyandu) cadres. In the context of program implementation, cadre behavioral factors, particularly attitudes and motivation, are important aspects that need to be reviewed to understand the quality of early stunting detection implementation. Highlighting that other contextual and structural factors influence success can help policymakers feel responsible and motivated to address these broader influences. This study aims to examine the attitudes and motivation of cadres in implementing the early stunting detection program at Posyandu. This study used an observational analytical design with a cross-sectional approach. The study sample consisted of 96 health cadres actively involved in implementing Posyandu activities. The variables studied included cadre attitudes and motivation as independent variables, and the ability to detect stunting as an indicator of program implementation. Data analysis was performed using univariate analysis, bivariate analysis using the Chi-square test, and multivariate analysis using logistic regression to assess the role of variables simultaneously. The results showed a significant relationship between cadre motivation and the ability to detect stunting early (p = 0.003), as well as between cadre attitudes and the ability to detect stunting early (p = 0.019). However, in a multivariate analysis, the attitudes and motivations of health cadres did not show a significant partial effect on the ability to detect stunting early. This finding suggests that the implementation of the early detection program for stunting at integrated health posts (Posyandu) is influenced not only by the attitudes and motivations of health cadres, but also by other contextual and structural factors.